Solve for v 11(9-v)=0

Math
11(9-v)=0
Divide each term by 11 and simplify.
Tap for more steps…
Divide each term in 11(9-v)=0 by 11.
11(9-v)11=011
Cancel the common factor of 11.
Tap for more steps…
Cancel the common factor.
11(9-v)11=011
Divide 9-v by 1.
9-v=011
9-v=011
Divide 0 by 11.
9-v=0
9-v=0
Subtract 9 from both sides of the equation.
-v=-9
Multiply each term in -v=-9 by -1
Tap for more steps…
Multiply each term in -v=-9 by -1.
(-v)⋅-1=(-9)⋅-1
Multiply (-v)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1v=(-9)⋅-1
Multiply v by 1.
v=(-9)⋅-1
v=(-9)⋅-1
Multiply -9 by -1.
v=9
v=9
Solve for v 11(9-v)=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top